2019
DOI: 10.5606/tgkdc.dergisi.2019.16867
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life after minimally invasive varicose vein treatment

Abstract: Bu kesitsel çalışmada varisli hastalarda minimal invaziv işlemler sonrasında yaşam kalitesindeki değişimler değerlendirildi. Ça lış m a pla nı: Çalışmaya minimal invaziv tekniklerle tedavi edilen varisli 150 hasta (58 erkek, 92 kadın; ort. yaş 47.1±12.0 yıl; dağılım 19-80 yıl) dahil edildi. Veriler hasta bilgi formları ve Venöz Yetmezlikte Epidemiyolojik ve Ekonomik Çalışma-Yaşam Kalitesi/Semptomlar Anketi kullanılarak toplandı. Minimal invaziv işlemlerden önce, hastalar varisler ve rahatlama amaçlı tıbbi yakl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…This complication has been very rarely reported in the literature and limited to a few case reports after appendectomy and mastectomy. [7] In these reports, the initial shape and wound characteristics and posttreatment healing period were similar to our case. To the best of our knowledge, there is no case report described in the literature after venous surgery.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This complication has been very rarely reported in the literature and limited to a few case reports after appendectomy and mastectomy. [7] In these reports, the initial shape and wound characteristics and posttreatment healing period were similar to our case. To the best of our knowledge, there is no case report described in the literature after venous surgery.…”
Section: Discussionsupporting
confidence: 84%
“…[6] It has been also suggested that mild skin trauma may initiate PG process. [7] In addition, PG may develop secondary to any surgical intervention. Autoimmunity, inflammation, and pathergy are the three main mechanisms in the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ey mentioned the heat sensation and discomfort when using the device. As an alternative to overcome these problems and enhance the compliance to compressive therapy, the authors highlighted the importance of nurses in the awareness regarding the bene ts of regular use of the elastic socks associated to changes in the life style 22 .…”
Section: Adversities That Permeate the Use Of Elastic Compression Socksmentioning
confidence: 99%